2018
DOI: 10.1186/s40100-018-0111-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting purchasing process of digestate: evidence from an economic experiment on Sicilian farmers’ willingness to pay

Abstract: In this study, we evaluate from the perspective of the theory of commitment costs if the level of farmer understanding about digestate attributes could influence the willingness to pay (WTP) for it. For this purpose, we carried out a research on a sample of 223 Sicilian farmers to correlate their WTP for digestate with a set of eight attributes which usually characterise organic soil conditioners. An experimental design was set up so that participants were given different waiting times to decide on their WTP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Sicily and other southern Italian regions are well behind the rest of the country in terms of anaerobic digestion plants and the agro-energy chain in general [45]. The production potential of bio-methane in many parts of southern Italy is undeveloped and even unknown despite being potentially very high [46].…”
Section: Discussionmentioning
confidence: 99%
“…Sicily and other southern Italian regions are well behind the rest of the country in terms of anaerobic digestion plants and the agro-energy chain in general [45]. The production potential of bio-methane in many parts of southern Italy is undeveloped and even unknown despite being potentially very high [46].…”
Section: Discussionmentioning
confidence: 99%
“…Etna area (Italy). A sample of 140 students participated in a non-hypothetical experimental auction which is a well-established method of assessing the WTP for food products (Lusk and Shogren, 2007;Pappalardo and Lusk, 2016;Wongprawmas et al 2016;Pappalardo et al 2017;Pappalardo et al, 2018;Selvaggi et al, 2018a and 20181b). This type of experiment offers the advantage of providing an incentive for participants to truly reveal their preferences.…”
Section: Experimental Designmentioning
confidence: 99%
“…Existing studies on the demand for fertilizer products derived from dairy manure are all based on responses from European producers; we know of no peer-reviewed study in US agriculture 1 . In a study conducted in Sicily, Pappalardo et al (2018) found that farmers' willingness-to-pay for digestate (a product of anaerobic digestion) was strongly influenced by how much information they had about the digestate. Pampuro et al (2018) conducted a survey and focus groups to determine farmers' attitudes toward using pelletized composted manure in Northwestern Italy and found that nitrogen content was the most important attribute to farmers.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Sicily, Pappalardo et al . (2018) found that farmers' willingness-to-pay for digestate (a product of anaerobic digestion) was strongly influenced by how much information they had about the digestate. Pampuro et al .…”
Section: Introductionmentioning
confidence: 99%